First report of Athelia rolfsii on Alstroemeria in Turkey - Polat, Zühtü; Gültekin, Mehmet Akif; Palacıoğlu, Gülsüm; Bayraktar, Harun (SPRINGER, 2022)
Alstroemeria spp. (Lily of the Inca, Peruvian Lily) is a cutting garden fower widely grown in many countries. In July 2021, symptoms of leaf chlorosis, wilting, root rot, and dark brown stem lesions near the soil level were observed on about 20% of Alstroemeria spp. plants in a greenhouse in Bursa province, Turkey. The pathogen produced abundant white, fufy mycelium and brown sclerotia on infected tissues.
Keywords: Alstroemeria; Athelia rolfsii; Stem rot